2007
DOI: 10.1111/j.1751-2409.2007.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Infra‐humanization: The Wall of Group Differences

Abstract: Infra‐humanizing outgroups involves considering outgroups less human and more animal‐like than the ingroup, which is perceived, in essence, as fully human. In this article, the first section presents the theoretical background of infra‐humanization and distinguishes it from related concepts, such as dehumanization. The three basic hypotheses of the theory are then presented with a summary of empirical evidence. Social implications follow. Reasons for the pervasiveness of the phenomenon are examined as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
328
2
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(350 citation statements)
references
References 79 publications
(129 reference statements)
8
328
2
12
Order By: Relevance
“…Most ingroup members are ethnocentric and believe that their group is fully human whereas they consider that many outgroups are less human. This phenomenon has been called infra-humanization (see Leyens, Demoulin, Vaes, Gaunt, & Paladino, 2007;Leyens et al, 2000). It does not mean that outgroups are denied any humanity, but refers to the way in which outgroup members are deprived of complete humanness by attributing them fewer uniquely human characteristics, such as secondary emotions (i.e., love, contempt) than to ingroup members (for reviews, see Demoulin et al, 2004;Leyens et al, 2007).…”
mentioning
confidence: 99%
“…Most ingroup members are ethnocentric and believe that their group is fully human whereas they consider that many outgroups are less human. This phenomenon has been called infra-humanization (see Leyens, Demoulin, Vaes, Gaunt, & Paladino, 2007;Leyens et al, 2000). It does not mean that outgroups are denied any humanity, but refers to the way in which outgroup members are deprived of complete humanness by attributing them fewer uniquely human characteristics, such as secondary emotions (i.e., love, contempt) than to ingroup members (for reviews, see Demoulin et al, 2004;Leyens et al, 2007).…”
mentioning
confidence: 99%
“…Por tanto, se sugiere que la infrahumanización o animalización se produciría cuando las personas reservan los sentimientos (tanto positivos como negativos) para su propio grupo y se los niegan al exogrupo. De esta forma, dado que junto a los sentimientos positivos también atribuyen más sentimientos negativos a su grupo, la deshumanización no debe ser entendida en términos de favoritismo endogrupal (Leyens, Demoulin, Vaes, Gaunt y Paladino, 2007). En otras palabras, si la deshumanización fuese una tendencia a beneficiar al endogrupo (Fiske, 2010), sólo se observaría una mayor atribución de sentimientos positivos (pero no negativos) al propio grupo.…”
Section: Dos Formas De Deshumanización: Animalización Y Mecanizaciónunclassified
“…Tal y como describen Leyens et al (2007), dicha elección venía respaldada por las siguientes razones: a) El estudio de los sentimientos había sido vinculado en menor medida al estudio del prejuicio y la discriminación; b) los sentimientos no dependen de las relaciones estructurales ni del status de los grupos; y c) los sentimientos no se ven afectados por la deseabilidad social. En esta línea, para poder captar la deshumanización, Leyens et al (2001) presentaron a los participantes un listado de sentimientos (emociones exclusivamente humanas) y emociones (compartidas con otras especies) con valencia positiva y negativa junto con palabras de relleno (relacionadas con sociabilidad y competencia).…”
Section: Dos Formas De Deshumanización: Animalización Y Mecanizaciónunclassified
See 1 more Smart Citation
“…Some emotions, called «secondary emotions» are typically human (e.g., nostalgia, guilt,...) whereas others (e.g., fear, joy), called «primary emotions», are common to both humans and animals. Leyens, Demoulin, Vaes, Gaunt, & Paladino (2007) have shown that people tended to routinely «infra-humanize» ougroups by attributing them fewer secondary emotions than their ingroup. Such a form of group perception seems particularly likely when the outgroup is potentially threatening to the ingroup.…”
Section: Stereotype Contentmentioning
confidence: 99%